Dispensasi Nikah dalam Perspektif Maslahah - Khalimi, Agus (Al-Hukkam: Journal of Islamic Family Law, 2021)
From a maslahah standpoint, this article examines the marital dispensation. The study's findings conclude that: 1) Marriage dispensation is a way to overcome the occurrence of early marriage through a permit procedure to the Religious Courts to get court approval, as stated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage.According to scholars, Islamic law does not recognize the term marriage dispensation because the criteria for marriage are when a person is mature and has good judgment, whereas Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law has determined that anyone under the age of 19 must apply for a marriage dispensation to obtain permission from the Relative. Religious Courts must weigh different issues, such as syar'i, sociological, psychological, legal, and health, when adjudicating cases of application for dispensation for marriage.2) Marriage dispensation is only granted if it does not conflict with the objectives of Islamic law (maqasidu al-shari'ah) in maintaining the safety of offspring (hifzhu al-nasl) at the al-daruriyyah level or at least al-hajiyyah, without jeopardizing the safety of the parties bound in the marriage bond (hifzhu al-nafs) (hifzhu alaql).